2017
DOI: 10.1111/ggi.12945
|View full text |Cite
|
Sign up to set email alerts
|

Femoral muscle mass relates to physical frailty components in community‐dwelling older people

Abstract: Femoral muscle mass influenced exercise capacity and physical frail components compared with calf muscle mass. These results suggest the importance of the femoral muscle in physical frailty. Geriatr Gerontol Int 2017; 17: 1636-1641.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 23 publications
3
13
0
3
Order By: Relevance
“…reported that femoral muscle mass influenced both peak VO 2 and HGS in community-dwelling older people [28], which may suggest an important role of training to increase femoral muscle mass in the improvement of HGS.…”
Section: Discussionmentioning
confidence: 92%
“…reported that femoral muscle mass influenced both peak VO 2 and HGS in community-dwelling older people [28], which may suggest an important role of training to increase femoral muscle mass in the improvement of HGS.…”
Section: Discussionmentioning
confidence: 92%
“…4,5 Thigh muscle is known as the primary agonist muscle of exercise and activities of daily life. Thigh muscle mass is found to be associated with sarcopenia-related indicators such as grip strength, knee extension muscle strength, walking speed, and TUG.…”
Section: Introductionmentioning
confidence: 99%
“…Thigh muscle mass is found to be associated with sarcopenia-related indicators such as grip strength, knee extension muscle strength, walking speed, and TUG. 4 While the importance of the thigh muscle is pointed out, the clinical significance of the thigh circumference is not fully understood. In addition, the possibility of using the thigh circumference as a sarcopenia screening tool has not been determined before.…”
Section: Introductionmentioning
confidence: 99%
“…Otros estudios con la temática de ejercicio físico con personas con EM hicieron sus investigaciones con valores de edad semejantes al presente estudio, de los cuales se puede citar En la composición corporal, es importante destacar los riesgos asociados con la grasa corporal total y la MM, ya que la composición de los segmentos corporales individuales son particularmente importantes para predecir el riesgo de algunas enfermedades. La adiposidad central aumentada, por ejemplo, puede estar asociada con enfermedad cardiometabólica, apoplejía y cáncer, mientras que la disminución de MM apendicular se asocia con caídas y fragilidad aumentadas (González et al, 2017;Scott et al, 2017;Takahashi et al 2017). Comparando a los datos porcentuales presentados por Wingo, Young, Motl (2017) (varones con EM 24,5±4,3 y mujeres con EM 36,4±7,7), donde se han observado diferencias significativas en todo el cuerpo y la composición corporal regional entre varones con IMC emparejados con y sin EM, y que los varones con EM tenían significativamente menos MM de cuerpo entero y mayor masa grasa.…”
Section: Discussionunclassified
“…En los valores del IMC encontrados en el presente estudio, se encuadran como normales en acuerdo con la OMS (2017) y están de acuerdo con la investigación realizada por Wingo, Young y Motl (2017) (varones con EM 23,6±2,5 y mujeres con EM 26,1±5,2). La composición corporal es importante para predecir el riesgo de algunas enfermedades, al mismo tiempo que la disminución de MM en los miembros superiores e inferiores se asocia con caídas y fragilidad aumentadas (González et al, 2017;Scott et al, 2017;Takahashi et al 2017).…”
Section: Características De La Muestra En Parejasunclassified